2015
DOI: 10.1007/s40279-015-0466-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Vertical Jump Potentiation: A Deterministic Model

Abstract: This review article discusses previous postactivation potentiation (PAP) literature and provides a deterministic model for vertical jump (i.e., squat jump, countermovement jump, and drop/depth jump) potentiation. There are a number of factors that must be considered when designing an effective strength-power potentiation complex (SPPC) focused on vertical jump potentiation. Sport scientists and practitioners must consider the characteristics of the subject being tested and the design of the SPPC itself. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 147 publications
3
49
1
9
Order By: Relevance
“…The exact nature of the mechanisms that influence muscle power development has not yet been fully elucidated, but there is evidence suggesting some factors that likely play a role in this process, namely relative strength, gender, muscle and neuromuscular characteristics, fatigue, and training time (44). Moreover, increased agonist muscle activation and motor unit firing frequency appear to be involved in enhanced power production (12).…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature of the mechanisms that influence muscle power development has not yet been fully elucidated, but there is evidence suggesting some factors that likely play a role in this process, namely relative strength, gender, muscle and neuromuscular characteristics, fatigue, and training time (44). Moreover, increased agonist muscle activation and motor unit firing frequency appear to be involved in enhanced power production (12).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is known as postactivation potentiation (PAP) and its use within the field of strength and conditioning has grown rapidly as performance enhancing effects have been demonstrated within athletic movements such as jumping (29,32) and sprinting (28). There are several suggested mechanisms behind PAP, including the recruitment of higher order motor units, increase in pennation angle, and the phosphorylation of myosin regulatory light chains (32).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, squat [13][14][15] , jump [16][17][18] and sprint 16,19,20 protocols stand out. In all of these studies, significant performance differences after potentiation protocol were found (p <0.05).…”
Section: Introductionmentioning
confidence: 99%